2017
DOI: 10.4103/jfmpc.jfmpc_24_17
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of menstrual hygiene among reproductive age women in South-west Delhi

Abstract: Background:The issue of menstrual hygiene is inadequately acknowledged in our nation. The use of sanitary pads and washing the genital area are essential practices for good menstrual hygiene. Poor menstrual hygiene may lead to itching or rashes in the perineal region, bad odor, and sometimes, major complications such as pelvic inflammatory disease and toxic shock syndrome. Therefore, the objective of this study was to assess the knowledge and practice of menstrual hygiene among reproductive age group women.Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 6 publications
0
15
2
Order By: Relevance
“…In contrast to the findings of the current study, some studies of women of reproductive age (Astuti et al, 2021;Budhathoki et al, 2018;Kumar et al, 2017;Patel, 2016;Varghese et al, 2015)medical students, and adolescent girls in India show that the majority women and girls used disposable sanitary napkins during menstruation instead of unhygienic rags and old clothes, tissue paper, or cotton/wool pieces. The possible reasons for this difference are that the women in those studies had good knowledge about MHM and financial capacity to buy sanitary napkins.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast to the findings of the current study, some studies of women of reproductive age (Astuti et al, 2021;Budhathoki et al, 2018;Kumar et al, 2017;Patel, 2016;Varghese et al, 2015)medical students, and adolescent girls in India show that the majority women and girls used disposable sanitary napkins during menstruation instead of unhygienic rags and old clothes, tissue paper, or cotton/wool pieces. The possible reasons for this difference are that the women in those studies had good knowledge about MHM and financial capacity to buy sanitary napkins.…”
Section: Discussioncontrasting
confidence: 99%
“…According to the United Nations Children's Fund (UNICEF), MHM is an integral part of hygiene for most women and girls (UNICEF, 2020) from menarche to menopause (Budhathoki et al, 2018). During menstruation, they need to maintain hygiene by adequately cleaning the external genitalia, using a clean cloth, a sanitary pad (or other products, e.g., tampon, cup) hygienically, and changing the pad or cloth every 3 to 4 hours (Hjelm et al, 2018;Kaur, 2018;Kumar et al, 2017). The use of unhygienic materials may adversely affect women's and girls' health and result in reproductive tract infections (RTIs) (Ulley et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…5 In our study 59% used sanitary pads which were less when compared to a study done by Kumar et.al in south Delhi where 91% used sanitary pads since Delhi is metropolitan city therefore there was better awareness of usage of sanitary pads. 6 65% of the study participants in our study reported atleast one symptom of RTI which was more when compared to a study done by Mani in Tamil Nadu where 33.3% reported atleast one symptom of RTI as majority belonged to Class III in our study when compared to Class II in Tamilnadu study. 7 In a study done by Balamurugan et al in Hubli, Karnataka, majority of women (32.7%) complained of abnormal vaginal discharge followed by lower backache in (31.4%) and lower abdominal pain in (23.5%) women.…”
Section: Discussioncontrasting
confidence: 65%
“…The prevalence of poor menstrual hygiene practice was 27.5 to 40% in Nepal studies [ 18 , 19 ] and 68.5% in Bangladesh [ 20 ]. It was also ranged between 44.8–81.7% in different studies conducted in India [ 21 – 24 ]. The prevalence of poor menstrual hygiene practice was 45.45% in Uganda [ 25 ], 74.7% in Nigeria [ 26 ], 28.8% in Kenya [ 27 ] and 69.9% in Ghana [ 28 ].…”
Section: Introductionmentioning
confidence: 99%